SUMBER HUKUM DAN RASIONALITAS DALAM EKONOMI ISLAM - Agustin, Aditya Dinar; Cantika Putri; Raihan Aghna Dzaki (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Islam is a comprehensive religion that regulates not only worship but also social and economic aspects of human life. Islamic economic law emerged as a reaction to the conventional system that prioritizes profit while often neglecting moral and spiritual dimensions. Through an examination of Islamic legal sources such as the Qur’an, Sunnah, Ijma’, and Qiyas, this study emphasizes that every economic activity in Islam must be grounded in justice, benefit, and balance. Using a qualitative descriptive-analytical approach based on literature studies from classical and modern works in Islamic economics, the research reveals that Islamic rationality is ethical and socially oriented, differing from secular rationality which focuses only on material gain. The integration between law and rationality shows that Islam provides an economic paradigm that is intellectually logical as well as spiritual, enabling the creation of an ethical, just, and prosperous economic system for humanity.